2014
DOI: 10.1071/bt14037
|View full text |Cite
|
Sign up to set email alerts
|

Seed storage behaviour of 101 woody species from the tropical rainforest of southern China: a test of the seed-coat ratio–seed mass (SCR–SM) model for determination of desiccation sensitivity

Abstract: The Xishuangbanna tropical rainforest in Yunnan Province is the greatest biodiversity hotspot in China. However, the biodiversity of this region is under threat, making seed conservation through seed and/or germplasm banking particularly urgent and crucial. Seed desiccation sensitivity limits the possibility of seed banking of 47% of tropical rainforest species. Thus, knowing if a species has desiccation-sensitive seeds is an important first step in seed banking; however, often resources are limited, making it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…Similarly, Pritchard et al [18] and Daws et al [19] respectively proposed 100-seed test and Seed-coat ratio–seed dry mass (SCR-SM) models for rapid seed storage behaviour assessment, particularly in woody species. An ongoing trend in SSB allocation has been the combination of several approaches resulting in more reliable conclusion [20, 21] and appeared relevant for the rapid and reliable study of the nearly 311,000 plant species for which information on seed storage physiology is still needed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Pritchard et al [18] and Daws et al [19] respectively proposed 100-seed test and Seed-coat ratio–seed dry mass (SCR-SM) models for rapid seed storage behaviour assessment, particularly in woody species. An ongoing trend in SSB allocation has been the combination of several approaches resulting in more reliable conclusion [20, 21] and appeared relevant for the rapid and reliable study of the nearly 311,000 plant species for which information on seed storage physiology is still needed [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we concluded that S. nux-vomica and S. potatorum seeds are desiccation-tolerant and those of S. benthamii are desiccation-sensitive. Lan et al (2014) and Sivakumar et al (2006) reported that seeds of S. nux-vomica are desiccationtolerant, while Warrier et al (2017) reported that seeds of S. potatorum are recalcitrant. These previous conclusions were based on the decrease in germination percentage of desiccated seeds.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, seeds of ~50% of the 101 woody species from Xishuangbanna (including native forest and cultivated species) were estimated to be desiccation‐sensitive (Lan et al 2014). Another study on 358 species of trees, shrubs, vines and herbs from various habitats in the same region showed that 88% of the species had dormant seeds (Lan et al 2018).…”
Section: Introductionmentioning
confidence: 99%